ANALISIS DINAMIKA KOALISI MENUJU PEMILIHAN UMUM PRESIDEN (PILPRES) 2024 - Efriza, SIP., M.Si, Efriza; Randisa, Aziz Reza; Lestari, Agisthia; Hanif, Fahmi Amanatul (Universitas Nasional, 2024)
This study discusses the coalition process and dynamics that occur in the coalition in the 2024 Presidential Election (Pilpres). The presidential and vice presidential nomination threshold provisions (presidential threshold) where the Election Law stipulates that presidential and vice presidential candidate pairs can be proposed by political parties or a coalition of political parties that have at least 20 percent of seats in the People's Representative Council (DPR) or 25 percent of valid national votes in the legislative election, are causes that also influence the pendulum movement of coalition formation. In addition, compensation for the position as a vice presidential candidate from the new coalition that is followed is also a consideration for the coalition. This study uses a descriptive qualitative method with an instrumental case study approach in the 2024 Presidential Election to explain the dynamics of political party coalitions. The results of the study show that the coalition ahead of the 2024 Presidential Election does not focus on policy preferences, or political parties do not pay serious attention to building a coalition based on ideology or public policy for the benefit of the people. Political parties tend to concentrate on how to gain power as a basis for building a coalition. Suggestion, majority political strength is needed to support a strong and effective government so it is important for political parties to form a permanently bound coalition or permanent electoral coalition. Abstrak Penelitian ini membahas proses koalisi dan dinamika yang terjadi dalam koalisi pada Pemilihan Umum Presiden (Pilpres) 2024 ini. Ketentuan ambang batas pencalonan presiden dan wakil presiden (presidential thereshold) dimana Undang-Undang Pemilu menetapkan bahwa pasangan calon presiden dan wakil presiden dapat diajukan oleh partai politik atau gabungan partai politik yang memiliki sekurang-kurangnya 20 persen kursi di Dewan Perwakilan Rakyat (DPR) atau 25 persen suara sah nasional dalam pemilu legislatif, merupakan penyebab yang turut mempengaruhi gerak bandul pembentukan koalisi. Selain itu, kompensasi jabatan sebagai calon wakil presiden dari koalisi baru yang diikuti juga menjadi pertimbangan koalisi. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus yang bersifat instrumental pada Pilpres 2024 untuk menjelaskan dinamika koalisi partai politik. Hasil penelitian menunjukkan bahwa koalisi menjelang Pilpres 2024 tidak berfokus pada preferensi kebijakan, atau partai politik tidak memperhatikan secara serius untuk membangun koalisi yang didasarkan pada ideologi atau kebijakan publik untuk kepentingan rakyat. Partai politik cenderung berkonsentrasi pada cara untuk mendapatkan kekuasaan sebagai dasar membangun koalisi. Saran, diperlukan kekuatan politik mayoritas untuk menopang pemerintahan yang kuat dan efektif sehingga penting bagi partai politik untuk membentuk koalisi yang diikat secara permanen atau koalisi elektoral permanen.